PERANAN SEKTOR AGROINDUSTRI TERHADAP PEREKONOMIAN PROVINSI RIAU: ANALISIS STRUKTUR INPUT-OUTPUT - Arnandasari, Pradita; Bakce, Djaimi; Restuhadi, Fajar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Agroindustry sector is a sector which play important roles in provide added value for agricultural products, employment and foreign exchange earner for the Riau Province.This study aims to analyze the role of agroindustry sector against the economy of Riau Province through input-output structure review. The data in this research is data input-output table of Â Riau Province basedthe price producers transactions in 2012 with 18 x 18 sector classification sourced from Bappeda of Riau Province. Analysis of the role of agroindustry sector is done through a review of the output and the input.The results show that:First, Agroindustrysector contributes highto the economy of the Riau Province. Secondly, in terms of output, component output establishment of agroindustry is driven by exports, intermediate output and consumption. Third, in terms of inputs, agroindustry sector is driven by the intermediate input, producer surplus and wages-salary.Based on these results, in order to encourage economic growth through the development of agroindustry sector it is necessary to the efforts of all parties involved, both government and private sector by developing agroindustry based commodities exports and increase direct investment that needs to be driven by the accumulation of capital from producer surplus. Â  Keywords: the role of agroindustry sector, input-output table, producer surplus